رہبانیت پرصوفیاءکی آراء اورناقدینِ تصوف کے نقد کا جائزہ : Revisiting Sufi and Their Critics Perspectives on Monasticism: An Analytical Review - Akram , Dr. Muhammad; Muhammad Saad , Muhammad Saad (Al-Amīr Research Journal for Islamic Studies, 2023)
This paper conducts a thorough review of the opinions of Sufi scholars and their critics regarding the concept of monasticism within Sufism. It delves into the historical context and philosophical underpinnings of Sufi ascetic practices, exploring the varying interpretations and applications of monastic ideals within the Sufi tradition. Additionally, the paper examines critiques leveled against Sufi monasticism by detractors, analyzing their arguments and assessing their validity in light of Sufi teachings and historical practices. Sufism, a mystical branch of Islam, has often been misunderstood and criticized, particularly in relation to its similarities and differences with monastic traditions. By examining primary Sufi texts, historical accounts, and scholarly analyses, this review elucidates the nuanced views of Sufi masters on asceticism, solitude, and spiritual practice. Furthermore, it critically evaluates common criticisms of Sufism, such as accusations of heresy, idolatry, and deviation from orthodox Islam. Through this exploration, the paper aims to foster a deeper understanding of Sufism and its rich spiritual heritage while addressing misconceptions and misrepresentations perpetuated by its critics. Keywords: Sufism, monasticism, solitude, spiritual, misconceptions, criticisms.